Discovering vanishing objects in POSS I red images using the Virtual Observatory. Issue 1 (13th June 2022) - Solano, Enrique; Villarroel, B; Rodrigo, C
ABSTRACT: In this paper, we report a search for vanishing sources in POSS I red images using virtual observatory (VO) archives, tools, and services. The search, conducted in the framework of the VASCO project, aims at finding POSS I (red) sources not present in recent catalogues like Pan-STARRS DR2 (limiting magnitude r = 21.4) or Gaia EDR3 (limiting magnitude G = 21). We found 298 165 sources visible only in POSS I plates, out of which 288 770 had a cross-match within 5 arcsec in other archives (mainly in the infrared), 189 were classified as asteroids, 35 as variable objects, 3592 as artefacts from the comparison to a second digitization (Supercosmos), and 180 as high proper motion objects without information on proper motion in G aia EDR3. The remaining unidentified transients (5399) as well as the 172 163 sources not detected in the optical but identified in the infrared regime are available from a VO compliant archive and can be of interest in searches for strong M-dwarf flares, high-redshift supernovae, asteroids, or other categories of unidentified red transients. No point sources were detected by both POSS-I and POSS-II before vanishing, setting the rate of failed supernovae in the Milky Way during 70 yr to less than one in one billion.